Klaik Türk Şiirinde Türkçe Sözcüklerde Med - (:unkn) unknown (My University, 2008)
Osmanlı aruz biliminde med, Arapça ve Farsça sözcüklerde bir uzun heceyi ya da sonu çift ünsüzle veya hemze ile biten bir heceyi bir uzun bir ktsa olmak üzere iki hece olarak okumaktır. Türkçede kısa heceyi uzun okuyarak imale yapmak zaten yanlıştır, bir de bu kısa heceyi iki hece olacak biçimde büsbütün uzatmak aruzda büyük yanlış, sayılır. Kimi divanlar bu gözle tarandığında şairlerin Türkçe sözcüklerde de med yaptıkları görülmüştür. Med yapılan sözcüklerin kökenleri incelendiğinde ise, bu sözcüklerin gerçekte uzun ünlülü olduktan anlaşılmıştır. Makalede, bu sözcükler örnek beyitler üzerinde gösterilecek ve bu durumun sebepleri irdelenmeye çalışılacaktır.

In the Ottoman aruz meter, 'med means reading a syllable, which is long and ends with double consonants or 'hemze' in Arabic and Persian words, as two syllables, one 'long' and one 'short'. In Turkish, reading a short syllable longer than a normal is a misuse. In the aruz meter this usage is entirely wrong. When a respected poet's collected works (divan) is considered, the usage of med is seen in Turkish words. When the roots of these words are studied, it is seen that the roots have long vowels. In this study, these words will be pointed out along with sample couplets and reasons of these usages will be investigated.
Turkish 'Med' Words in Classical Turkish Literature
Keywords: Antropoloji